Effect of model scale on predicting illusory stereo depth effect of luminance contrast in real and virtual environments. Issue 1 (31st December 2016) - Tai, Nan-Ching
Abstract: Luminance contrast has been identified as an effective depth cue for creating illusory depth effects in scenes and has been validated as a design strategy for enriching spatial experience. To evaluate the effect of complex lighting in a design proposal, computer simulations and physical models are commonly used in the design process. However, computer simulations must provide perceptual reality, and physical models are often constructed at a reduced scale. Thus, validating the perceptual realism of a computer simulation and the effective range of the depth cue provided by luminance contrast is crucial. In this study, psychophysical experiments are conducted to compare the visual realism offered by computer simulations and physical models according to differences in scale. The results demonstrate that computer simulations can provide the necessary visual realism to create an illusory depth effect, and that the influence of model scale (whether full or reduced) on the depth effect is insignificant.